2022
DOI: 10.1183/13993003.00009-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 protective face masks and wearing durations on respiratory haemodynamic physiology and exhaled breath constituents

Abstract: BackgroundWhile assumed to protect against coronavirus transmission, face-masks may have effects on respiratory-haemodynamic parameters. Within this pilot study, we investigated immediate and progressive effects of FFP2 and surgical masks on exhaled breath constituents and physiological attributes in 30 adults at rest.MethodsWe continuously monitored exhaled breath profiles within mask space in older (age: 60–80 years) and young to mid-aged (age: 20–60 years) adults over the period of 15 and 30 min, respective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
68
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 82 publications
10
68
1
Order By: Relevance
“…Concerning the risk of hypoxia, several evaluations found that blood oxygen saturation decreases when donning face masks, and even more noticeably when wearing them for long periods or during physical activity. 11 , 22 , 23 , 40 In contrast, the present study was performed at rest and for a short time, during which the recorded levels of CO 2 did not substantially alter blood oxygen saturation, as in similar studies. 13 , 14 , 41 Nevertheless, the exposure to inhaled air CO 2 values higher than 5000 ppm, for long periods, is considered unacceptable for the workers, and is forbidden in several countries, 30 because it frequently causes signs and symptoms such as headache, nausea, drowsiness, rhinitis, and reduced cognitive performance.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Concerning the risk of hypoxia, several evaluations found that blood oxygen saturation decreases when donning face masks, and even more noticeably when wearing them for long periods or during physical activity. 11 , 22 , 23 , 40 In contrast, the present study was performed at rest and for a short time, during which the recorded levels of CO 2 did not substantially alter blood oxygen saturation, as in similar studies. 13 , 14 , 41 Nevertheless, the exposure to inhaled air CO 2 values higher than 5000 ppm, for long periods, is considered unacceptable for the workers, and is forbidden in several countries, 30 because it frequently causes signs and symptoms such as headache, nausea, drowsiness, rhinitis, and reduced cognitive performance.…”
Section: Discussionmentioning
confidence: 70%
“…19 Early markers of hypoventilation were observed after the 12-minute walking test among 22 children wearing FFP2 respirators, 20 , 21 after the 6-minute walking test among 100 adults wearing surgical masks, 22 and even at rest in 30 adults and elderly with both types of masks. 23 …”
Section: Introductionmentioning
confidence: 99%
“…The analysis of volatile organic compounds (VOCs) in human breath offers vast possibilities for the development of non-invasive diagnostic techniques (Miekisch et al, 2004). Breath biomarkers could provide new and unique insights into metabolic (Sukul et al, 2018;2022b), physiological (King et al, 2010b;Sukul et al, 2016Sukul et al, , 2022a or pathophysiological processes (Nakhleh et al, 2017;Trefz et al, 2019;Löser et al, 2020). VOCs are exhaled shortly after their production and may therefore deliver systemic information quickly and noninvasively.…”
Section: Introductionmentioning
confidence: 99%
“…An optimized methodology and/or protocol for reliable and repeatable real-time and offline breathomics under COVID-19 condition as well as additional mandatory safety measures will induce analytical confounders and will increase systematic errors. For instance, we have recently demonstrated immediate and progressive effects of medical face-masks (surgical and FFP2) on exhaled VOCs compositions in healthy adults aged between 20 and 80 years 27 . Therefore, measurements within mask space cannot be attributed for reproducible sampling.…”
Section: Introductionmentioning
confidence: 99%